Nilai Pancasila dalam Metode Penemuan Hukum: Orientasi dan Konstruksi Nilai Pancasila dalam Rechtsvinding - Amin, Fakhry (Ajudikasi : Jurnal Ilmu Hukum, 2023)
This study examines the role of Pancasila values in the process of legal discovery or rechtsvinding in Indonesia. Pancasila, as the foundational philosophy of the Republic of Indonesia, holds a crucial position in shaping the nation's identity, character, and developmental direction. Beyond being a philosophical underpinning of the state, Pancasila's values serve as guiding principles in the life of the nation, state, and society. Within the legal context, Pancasila is highly relevant in the rechtsvinding process, which involves searching for laws related to specific cases or situations.The research utilizes normative methods with a philosophical and analytical approach. Data is gathered through literature studies, analyzing legal norms, regulations, and relevant legal works. The primary goal is to analyze how Pancasila values manifest in the rechtsvinding approach and their impact on legal stability and justice in the Indonesian legal system.The study findings reveal that Pancasila values play a central role in the rechtsvinding process. These values influence the interpretation and application of the law by judges and legal practitioners. The 1945 Constitution reflects Pancasila values in its principles that form the basis of state law and policy. Articles within the constitution embody Pancasila values like social justice, balance of rights and responsibilities, and human rights protection. Furthermore, Pancasila values significantly contribute to legal stability, fostering certainty and harmony in the Indonesian legal system. The integration of Pancasila principles in the rechtsvinding process guides decision-making with a focus on justice, unity, and equality.